The PCT to Albumin Ratio Predicts Mortality in Patients With Acute Kidney Injury Caused by Abdominal Infection-Evoked Sepsis - Chen, Lijuan; Wu, Xiaoli; Qin, Haiyan; Zhu, Hongchao (Frontiers in Nutrition, 2021)
Purpose: Considerable evidence suggests that inflammation and malnutrition are common in patients with acute kidney injury (AKI) and correlated with mortality of various diseases. Despite this, few studies have reported the underlying predictive effects of inflammatory and nutritional markers in combination on the mortality of AKI patients. Herein, we aimed to explore the values of PCT and CRP as well as the ratios of PCT/Alb and CRP/Alb in the poor prognosis of patients with sepsis-induced AKI. Patients and Methods: A total of 171 patients with AKI, caused by abdominal infection-evoked sepsis, were retrospectively studied and divided into a survival group (107 cases) and a non-survival group (64 cases). Univariate analysis was used to compare the clinical data of the two groups. Multivariate logistic regression analysis was used to analyze the independent risk factors of poor prognosis in patients with sepsis-induced AKI. The ROC curve was used to evaluate the diagnostic value of PCT, CRP, PCT/Alb, and CRP/Alb in the poor prognosis of patients with sepsis-induced AKI. Results: Univariate analysis revealed that the values of PCT, CRP, CRP/Alb, and PCT/Alb were significantly different between AKI survival and non-survival groups, and further analysis found that PCT and PCT/Alb were independent risk factors for poor prognosis in patients with sepsis-induced AKI after adjusting with age and gender. Of note, the predictive accuracy (0.864 vs. 0.807), specificity (83.2 vs. 69.2), and sensitivity (79.7 vs. 76.6) of PCT/Alb were all higher than that of the simple PCT. Conclusions: The ratio of PCT to Alb is an independent risk factor possessing a robust and accurate risk assessment for the poor prognosis of patients with sepsis-induced AKI, and it offers the potential to improve the management of this type of disease and a lower resultant mortality.